2021
DOI: 10.1111/febs.16241
|View full text |Cite
|
Sign up to set email alerts
|

Balancing life and death: BCL‐2 family members at diverse ER–mitochondrial contact sites

Abstract: The outer mitochondrial membrane is a busy place. One essential activity for cellular survival is the regulation of membrane integrity by the BCL‐2 family of proteins. Another critical facet of the outer mitochondrial membrane is its close approximation with the endoplasmic reticulum. These mitochondrial‐associated membranes (MAMs) occupy a significant fraction of the mitochondrial surface and serve as key signaling hubs for multiple cellular processes. Each of these pathways may be considered as forming their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 500 publications
1
16
0
Order By: Relevance
“…Previous studies reported that BOK, in contrast to BAX and BAK, mainly localizes to the ER and Golgi [19] and that it accumulates at the contact sites between the ER and mitochondria, where it plays a role in regulating calcium fluxes between the two organelles [38,39]. This is in agreement with our data in Fig.…”
Section: Bok Forms Ring-like Structures In Apoptotic Mitochondriasupporting
confidence: 94%
“…Previous studies reported that BOK, in contrast to BAX and BAK, mainly localizes to the ER and Golgi [19] and that it accumulates at the contact sites between the ER and mitochondria, where it plays a role in regulating calcium fluxes between the two organelles [38,39]. This is in agreement with our data in Fig.…”
Section: Bok Forms Ring-like Structures In Apoptotic Mitochondriasupporting
confidence: 94%
“…Of note, since the mitochondrial localization of Bax and Bak is required but not sufficient to the MOMP, the functional consequences of the interactions between anti-apoptotic Bcl-2s and TOMs are certainly highly dependent on the cellular context, governing the completion of Bax and Bak full activation. The role played by MAM in this regulation is currently under investigation and will certainly improve our understanding of this highly complex regulation network ([ 134 ], for an exhaustive review).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, B-cell lymphoma 2 (Bcl-2) and B-cell lymphoma-extra large (Bcl-X L ), two Bcl-2 family members on MAMs, connect with central modulatory domain of IP 3 Rs to suppress Ca 2+ release or indirectly inhibit IP 3 Rs through regulating its phosphorylation. Besides, both Bcl-2 and Bcl-X L can conjugate with VDAC1 to suppress mitochondrial Ca 2+ intake [ 63 ]. Moreover, myeloid cell leukemia factor-1 (Mcl-1), another anti-apoptotic protein of Bcl-2 family, not only restrains IP 3 R-mediated Ca 2+ release but also binds with VDACs to modulate mitochondrial Ca 2+ uptake.…”
Section: Mams and Cell Deathmentioning
confidence: 99%